A cross-sectional analysis based on GBD data: trends in the global, regional, and national burden of pelvic organ prolapse from 1990 to 2021 - Wang, Rui; Li, Wangshu; Yang, Jinliang; Aziz, Aziz ur Rehman; Ha, Chunfang (Frontiers in Public Health, 2025)
BackgroundPelvic organ prolapse (POP) is a prevalent condition affecting millions of women globally. Understanding its temporal trends and regional disparities is essential for effective public health interventions.MethodsA cross-sectional analysis was conducted using data from the Global Burden of Disease (GBD) study, examining trends in POP incidence, mortality, and disability-adjusted life years (DALYs) from 1990 to 2021. We analyzed the estimated annual percentage change (EAPC) and explored the association with the socio-demographic index (SDI).ResultsFrom 1990 to 2021, global POP cases increased from approximately 8.4 million to 14.0 million, while the age-standardized incidence rate (ASIR) declined from 374.84 to 317.51 per 100,000 population (EAPC = −0.46). Deaths rose from 281 to 486, but the age-standardized death rate (ASDR) remained stable. DALYs increased from 232,432 to 389,358, with a decrease in age-standardized DALY rate (EAPC = −0.59). Low-SDI regions exhibited the highest ASIR, ASDR, and DALYs in 2021.ConclusionThe global burden of pelvic organ prolapse has increased in absolute numbers, although age-standardized rates have declined. Low-SDI regions continue to face the highest burden, highlighting the need for targeted healthcare interventions.